On Chawton House - Yandle, Emma (Romanticism on the Net, 2023)
Curator Emma Yandle identifies the most Romantic object in the Chawton House collection as Mary Robinson’s Lyrical Tales, a slim volume published in 1800, just months before the writer’s untimely death at forty-three years old. Robinson was an eighteenth-century actress, celebrity, and writer, who has long been mostly remembered for her relationship with the Prince of Wales (later George IV), who fell in love with her on stage as Perdita in The Winter’s Tale. In recent decades, she has been reclaimed as one of the most important and overlooked writers of the period. Deeply inspired by the radical poetics of Wordsworth and Coleridge’s Lyrical Ballads, Robinson’s final poems are a marked departure: interweaving her command of metre, flair for narrative, and embrace of the Gothic into tales of ordinary women, refugees, and social outcasts. This short film introduces Robinson and the tragic story of her life; examines Chawton House’s copy of Lyrical Tales as a material object; and traces the repeated motif of the gravestone through Robinson’s poetry to her own final resting place—with its self-authored epitaph—in the graveyard of Old Windsor Church.